QUALITY CHARACTERISTICS OF DOUGLAS FIR STEMS (Pseudotsuga menziesii) FOR THE PRODUCTION OF MASSIVE WOOD MATERIALS - Trichkov, Neno; Koynov, Daniel; Ranov, Cvetelin (Innovation in Woodworking Industry and Engineering design, 2018)
The expansions of the raw material base for solid wood materials production are particularly important in terms of wood deficit and increased consumption. The aim is to use solid wood materials production like replacement wood, which doesn’t deteriorate the performance of the finished products, as well as technical and economic production parameters. The Douglas fir (Pseudotsuga menziesii) is non popular wood species for Republic of Bulgaria. The studies for our country show that this tree species well adapted in these conditions, particularly in areas with high humidity. This gives reason to believe that this tree species is perspective for the production of solid wood materials.This report presents the results of studies about the size and quality characteristics of Douglas fir stems.